Revolutionizing Agricultural Water Management through AI-Driven Irrigation Systems: A Comprehensive Framework for Sustainable Farming Practices - Mole, Maheshkumar (International Journal of Computing and Engineering, 2025)
Global agricultural water management faces unprecedented challenges as traditional irrigation practices demonstrate substantial inefficiencies while water scarcity threatens food security worldwide. Artificial intelligence technologies integrated with Internet of Things sensors, machine learning algorithms, and automated control systems present transformative solutions for precision irrigation management across diverse farming environments. Smart irrigation frameworks utilize real-time soil moisture monitoring, weather pattern analysis, and crop physiological assessment to optimize water application timing and quantity while minimizing resource waste. Machine learning applications, including Random Forest, Support Vector Machines, Artificial Neural Networks, and XGBoost algorithms, process complex agricultural datasets to generate predictive models for crop water requirements and automated decision-making systems. Implementation of AI-driven irrigation technologies demonstrates remarkable water conservation achievements, substantial crop yield improvements, enhanced product quality, and significant economic benefits for agricultural producers through reduced operational costs and improved resource efficiency. Environmental sustainability benefits encompass enhanced soil health, reduced nutrient pollution, and improved agricultural ecosystem resilience while supporting carbon sequestration processes. Case studies across diverse agricultural regions validate the broad applicability and effectiveness of intelligent irrigation systems for addressing water management challenges in different farming contexts while promoting sustainable agricultural intensification necessary for global food security.